Redo laparoscopic pyeloplasty for recurrent ureteropelvic junction obstruction: Propensity score matched analyses of a high-volume center - Li, Jiayi; Yang, Yang; Li, Zonghan; Fan, Songqiao; Wang, Xinyu; Yang, Zhenzhen; Liu, Pei; Song, Hongcheng; Zhang, Weiping (Frontiers in Pediatrics, 2022)
Purpose: Review the experience of redo laparoscopic pyeloplasty (RLP) in patients with recurrent ureteropelvic junction obstruction (UPJO) in comparison to primary laparoscopic pyeloplasty (PLP) and redo open pyeloplasty (ROP), and determine the feasibility and effectiveness of RLP for recurrent UPJO in children. Methods: We retrospectively reviewed the clinical data of patients treated with transperitoneal PLP, RLP, and ROP for UPJO from December 2015 to December 2022. The Propensity score matching (PSM) was used to balance confounding variables. RLP patients were 1:4 matched with PLP and 1:3 matched with ROP. The primary outcomes were failure and postoperative complications. Complications were classified according to the Clavien-Dindo grading system. Results: The study included ten patients who underwent RLP, 43 patients who underwent ROP, and 412 patients who underwent PLP. The follow-up time ranged from 6 to 36 months in the RLP group, 12 to 60 months in the PLP group, and 24 to 54 months in the ROP group. In the RLP group, no failure but three postoperative complications (Clavien grade II) were observed during the follow-up. Compared with the PLP group, the older age, higher weight, larger preoperative anteroposterior diameter (APD) and APD/cortical thickness (P/C ratio), longer operation time, and postoperative length of stay (LOS) in the RLP group (P<0.05). After PSM, longer operation time and postoperative LOS were observed in the RLP group (P<0.05). Compared with the ROP group, the older age, higher weight, and longer postoperative LOS in the RLP group (P<0.05). After PSM, longer postoperative LOS was observed in the ROP group (P<0.05). The failure and complication rates were comparable between RLP and PLP, or RLP and ROP (P>0.05). Conclusions: Our result demonstrated that RLP performed as well as PLP except for a longer operation time. Compared with ROP, RLP has the advantages of a clearer surgical view, sufficient exposure, clearer anatomical landmark position, and minor trauma with a comparable clinical outcome. On experienced hands, RLP for recurrent UPJO after is a safe and effective procedure and should be considered an excellent alternative to the more commonly recommended ROP in select patients.